Respostas
respondido por:
1
Resposta:
4) Letra b
5) Letra b
Explicação passo a passo:
Nesses casos, faz-se necessário fazer a distributiva.
4- (3x-1)(5x²+2) = 15x³+6x-5x²-2
5- -2x²(5x-1) = -10x³+2x²
respondido por:
1
Resposta:
4) (3x-1)×(5x² +2) =15x³+6x-5x²-2
Calculo
3x × 5x² = 15x³
3x ×(+2)= +6x
-1× 5x² = -5x²
-1× (+2)=-2
Alternativa b)
5) -2x²(5x -1 ) = -10x³ +2x²
Calculo
-2x²× 5x = -10x³
-2x²× (-1)= +2x²
Alternativa b)
Explicação passo-a-passo:
Espero ter ajudado
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás